Heavy metals in tuna species meat and potential consumer health risk: A review - A A, Norhazirah; N A M, Shazili; Yunus, Kamaruzzaman; Sim, S F; A, Ahmad; Ong, M C (2020)
Marine fishes are one of the protein sources and they form a significant part of human diet around the world. In particular, tuna fisheries are considered as the largest and most specialized commercially important group of species among all commercial fishes. The preparing tuna methods such as cooking and canning might alter the level of heavy metals inside the meat. The heat that applied to the meat might be decreased the moisture content in tuna meat, thus give some effects to the heavy metal level. Other than that, the different composition and function of different parts of tuna can contribute to the various level of heavy metals analysed. The metal contamination in tuna species meat has put serious question to the safety level of fish intake to the community. It represent an abiding threat to human health as it has been linked to some adverse health effects such as mental retardation, kidney damage, and various types of cancer and even worse, death could occur.The following review articles presents the findings of the work carried out by the various researchers in the past on the heavy metal pollution in samples of Tuna species around the world.